2019
DOI: 10.1155/2019/8512028
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 Innate Lymphoid Cells Participate in Renal Fibrosis in Diabetic Kidney Disease Partly via TGF-β1 Signal Pathway

Abstract: Aim. To explore the role of group 2 innate lymphoid cells (ILC2s) in the pathogenesis of renal fibrosis in diabetic kidney disease (DKD). Methods. The proportion of ILC2s and the levels of Th2 cytokines (IL-4, IL-5, and IL-13) in the peripheral blood of normal control subjects (NC) or patients with type 2 diabetes mellitus (DM), early diabetic kidney disease (DKD1), or late diabetic kidney disease (DKD2) were analyzed by flow cytometry and ELISA. The expression of transforming growth factor-β1 (TGF-β1), fibron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The fourth ECCO guidelines state that IL-13 activates the TGF- β 1/Smad3 pathway as the central process in intestinal fibrosis formation [ 21 ]. It is reported that IL-4 and IL-13 can synergize with high glucose to promote the expression of TGF- β 1, FN, and collagen I in cultured HK-2 cells, indicating that the secretion of Th2 cytokines (IL-4 and IL-13) and the upregulated expression of TGF- β 1 are key factors in the development of renal fibrosis [ 39 ]. Another study showed that IL-13 induces fibrosis through the activation of TGF- β 1, and the synergistic effect of IL-13 and TGF- β 1 may increase the expression of eotaxin in human fibroblast [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth ECCO guidelines state that IL-13 activates the TGF- β 1/Smad3 pathway as the central process in intestinal fibrosis formation [ 21 ]. It is reported that IL-4 and IL-13 can synergize with high glucose to promote the expression of TGF- β 1, FN, and collagen I in cultured HK-2 cells, indicating that the secretion of Th2 cytokines (IL-4 and IL-13) and the upregulated expression of TGF- β 1 are key factors in the development of renal fibrosis [ 39 ]. Another study showed that IL-13 induces fibrosis through the activation of TGF- β 1, and the synergistic effect of IL-13 and TGF- β 1 may increase the expression of eotaxin in human fibroblast [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang et al indicated that adipose tissue-resident ILC1s, via the production of IFN-γ, promote tissue fibrosis and induce diabetes in obese individuals (185). Liu et al have demonstrated that the numbers of ILC2s as well as serum cytokine levels of IL-4, IL-5, and IL-13 are significantly elevated in diabetic kidney disease patients and have a positive correlation with disease severity (186). They further demonstrated that ILC2s, through the TGF-β1 signaling pathway, are involved in renal fibrosis seen in diabetic kidney disease (184).…”
Section: Innate Lymphoid Cells (Ilcs)mentioning
confidence: 99%
“…A recent study indicated that blood ILC2s are upregulated in ESRD patients (62); however, it is unclear if this elevation is related to ESRD pathogenesis. Moreover, it has also been reported that changes of blood ILC correlate with the severity of DN and LN (63,64). Further investigation is required to determine whether human renal ILC2s are friend or foe in kidney diseases.…”
Section: Renal Ilc2 and Diseasesmentioning
confidence: 99%
“…In addition, Liu et al. have been reported that ILC2 was negatively correlated with eGFR level in diabetic kidney disease patient with promoting renal fibrosis ( 63 ). Although it is not well understood whether Areg produced from ILC2 contribute to progress renal fibrosis, Areg expression is required for fibrosis induced by TGF-b overproduction.…”
Section: Ilc2 Contribute To Progression Of Renal Fibrosis?mentioning
confidence: 99%